The Dynamics of Local Politics and Preferences of Generation Z Students in the 2024 Presidential Election in North Sulawesi - Rifani, Irfan; Lobja, Xaverius Erick; Ramadhan, Muhamad Isa (UIN Sunan Gunung Djati, 2024)
The political geography of North Sulawesi provides insights into the local political dynamics with specific geographic considerations. This research employs a quantitative method, focusing on voter rationality, social identity, social cognition, social change, and political alternatives. Findings indicate that Generation Z students choose candidates based on vision, mission, performance, and digital information. Despite positive perceptions of performance, there is a discrepancy with the level of interest. Voter rationality is more focused on individual assessment than party loyalty. Social identity, including ethnic, religious, and cultural diversity, plays a role in political decision-making. Social media serves as the primary source of information, but voters actively seek verification from other sources. Mental processes and social cognition influence the interpretation of political information, and awareness of choosing in line with values, interests, expectations, and believed changes. Although voters have convictions, there is potential uncertainty in their choices. This study provides insights into political geography, voter behavior, and the socio-political context in North Sulawesi, supporting a deeper understanding of local political dynamics and student preferences.